Pengembangan Media Video Animasi Berbasis Powtoon pada Materi Statistika - Fenty Tiara Junika; Tatang Muhajang; Yudhie Suchyadi (STKIP Andi Matappa Pangkep, 2023)
Learning media is a tool in the teaching and learning process provided by the teacher regarding the material being taught to increase interaction between teachers and students and eliminate boredom in participating in learning so that it can encourage the learning process, therefore students need the development of learning media. This study aims to produce animation video media products based on Powtoon on statistics material in class IV SDN 21 Hanging with a total response of 18 students for the 2021/2022 academic year. This study uses the ADDIE model (analysis, design, development, implementation, evaluation). Field trials were carried out only on a limited basis. The instrument used in this study consisted of an expert validation sheet and a student response questionnaire instrument. The data analysis technique consists of an analysis of the feasibility of learning media. The results showed that the animation video based on Powtoon that was developed was feasible to be used as a learning media in class IV in statistics learning based on the average value of material expert validation of 93.33% and the average value of media validation of 77.14% and an average value of 77.14%. The average value of the language is 86.66%.